2014
DOI: 10.3389/fevo.2014.00037
|View full text |Cite
|
Sign up to set email alerts
|

The composition of cuticular compounds indicates body parts, sex and age in the model butterfly Bicyclus anynana (Lepidoptera)

Abstract: Chemical communication in insects' sexual interactions is well-known to involve olfaction of volatile compounds called sex pheromones. In theory, sexual chemical communication may also involve chemicals with low or no volatility exchanged during precopulatory gustatory contacts. Yet, knowledge on this latter type of chemicals is so far mostly restricted to the Drosophila fly model. Here we provide the most comprehensive characterization to date of the cuticular chemical profile, including both volatile and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 96 publications
2
43
2
Order By: Relevance
“…Together with the recent results on cuticular compounds in B. anynana (Heuskin et al. ), as well as former studies on Argynnis , and longstanding observations of mating behavior at short range, our study calls for assessing the relevance of female chemical cues for intraspecific and interspecific sexual interactions not only in moths but also in butterflies.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Together with the recent results on cuticular compounds in B. anynana (Heuskin et al. ), as well as former studies on Argynnis , and longstanding observations of mating behavior at short range, our study calls for assessing the relevance of female chemical cues for intraspecific and interspecific sexual interactions not only in moths but also in butterflies.…”
Section: Discussionsupporting
confidence: 80%
“…In another butterfly species, Bicyclus anynana , the composition of cuticular compounds in females differs between body parts and covaries with age (Heuskin et al. ). Our experiments with hybrid females show that the intensity of H. timareta male courtship is correlated with chemical composition of the presented female, supporting that male courtship decision relies on particular and species‐divergent female chemical cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). We used 8e10-day-old virgin males as all three components of the male sex pheromone, which is a major secondary sexual trait under sexual selection, are present at significant levels in the male blend at this age (Heuskin et al, 2014;Nieberding et al, 2008Nieberding et al, , 2012. We used 3e5-day-old virgin females as they readily mate in the laboratory (Brakefield et al, 2009;Nieberding et al, 2008Nieberding et al, , 2012.…”
Section: Methodsmentioning
confidence: 99%
“…Despite growing evidence that these compounds provide essential protection against desiccation and are used for communication in taxa such as Hymenoptera, Coleoptera, and Lepidoptera (Guerrieri et al 2009; Heuskin et al 2014; Zhang et al 2014, little is known about the nature and biological function of CHCs in Psylloidea. We have shown that the CHC profile of A. dobsoni is dominated by n alkanes, monomethyl , and dimethyl alkanes.…”
Section: Discussionmentioning
confidence: 99%